Mid-Holocene climate change and landscape formation in Ireland: Evidence from a geochemical investigation of a coastal peat bog. (July 2017) - Jordan, S.F.; Murphy, B.T.; O'Reilly, S.S.; Doyle, K.P.; Williams, M.D.; Grey, A.; Lee, S.; McCaul, M.V.; Kelleher, B.P.
Highlights: Elemental, GC–MS and GC-IRMS analysis of organic matter (OM) from a coastal peat bog. Changes in climate over a ca. 3400 yr period during the mid-Holocene. Evidence of the 4.2 ka event and Subboreal-Subatlantic transition in Ireland. Implications for environmental conditions resulting in formation of a 'drowned' forest landscape. Abstract: Following a period of unusually strong winds and high seas in the spring of 2014, a blanket peat bog formerly covered by a beach comprised of fine sand and large rocks was uncovered at a coastal site in Spiddal, Co. Galway, Ireland. The surface of the bog was littered with standing tree stumps, the remnants of a Holocene forest that had succumbed to a relatively sudden drowning. A combination of inorganic and organic geochemical techniques was applied to determine the cause of this rapid submersion and to glean palaeoclimatic information from the preserved record within the peat. The study represents the first use of a multiproxy lipid biomarker approach to investigate palaeoclimate conditions from a peat bog in Ireland. The results provide evidence of climatic variation throughout a ca. 3400 yr timeframe during the mid-Holocene. Biomarker proxies displaying the relative contribution of Sphagnum spp . vs. higher plants were used to show changes in precipitation and temperature during peat formation. The data correlate with described events, including the 4.2 ka event and the Subboreal-Subatlantic transition and show the benefit of a lipid biomarker method for investigating Ireland's peatland resources. In particular, the indication of colder/wetter conditions coinciding with the 4.2 ka event implies the possibility that its effects were felt in Ireland, contrary to some reports. The results suggest that a combination of warm and dry conditions followed by a rapid rise in sea level led to the growth and subsequent drowning of the ancient forest landscape.